Functionalization of anthracene: A selective route to brominated 1,4-anthraquinones - Berkil Akar, Kiymet; Cakmak, Osman; Büyükgüngör, Orhan; Sahin, Ertan (Beilstein Journal of Organic Chemistry, 2011)
Efficient and stereoselective syntheses are described for the preparation of 2,3,9,10-tetrabromo-1,4-dimethoxy-1,2,3,4-tetrahydroanthracenes 7, 8 and the corresponding 1,4-diol 17 by silver ion-assisted solvolysis of hexabromotetrahydroanthracene 6. Base-promoted aromatization of 7 and 8 afforded synthetically valuable tribromo-1-methoxyanthracenes 10 and 11. The reaction of 17 with sodium methoxide generated tribromodihydroanthracene-1,4-diol 27, whose oxidation with PCC gave 2,9,10-tribromoanthracene-1,4-dione (28). Therefore a selective and efficient method was developed for the preparation of compound 28 starting from 9,10-dibromoanthracene (1), in a simple four-step process. Compounds 10 and 11, and diol 27 constitute key precursors for the preparation of functionalized substituted anthracene derivatives that are difficult to prepare by other routes. The studies also reveal the broad range of reactivity and selectivity of the stereoisomeric anthracene derivatives.
Keywords: anthracene derivatives; anthracene-1,4-dione; aromatization; bromination; bromoanthracene; methoxyanthracene; silver-induced substitution